O-214 New Study of 529 Donor-Conceived Adults. (30th June 2022) - Kramer, W
Abstract: Study question: Does how and when a donor-conceived person (DCP) learns about their conception significantly affect their experiences and choices, including whether they'd consider using a donor or donating their own gametes? Summary answer: DCP are more likely to have neutral/positive feelings if told at a very young age about their donor origins by a family member. What is known already: DCP have reported that knowing about the methodology of their conception from an early age is optimal. Study design, size, duration: A cross-sectional survey of adult DCP was disseminated to registered users of the Donor Sibling Registry (DSR) in 2021. The survey consisted of 31 items including whether experience as DCP was positive or negative, the willingness to use donor gametes if spontaneous conception was not an option, and included questions regarding donating gametes. Participants/materials, setting, methods: 529 people (81.7% female) completed the survey. The median age was 28 years (range 18-77 years) and 94.7% were conceived via donor sperm. Main results and the role of chance: Most felt "neutral" (31.6%), "positive" (26.3%) or "very positive" (20.8%) about being a DCP regardless of donor type (sperm vs. oocyte vs. embryo). While most found out about being a DCP after age 18 (63.4%), those with a positive experience were more likely to "have always known" (40.7%). Those with a positive experience were not more likely to consider the donor a relative (46.4%) or have an ongoing relationship with one or more half-siblings from the same donor (24.5%). A negative experience being a DCP was associated with having medical complications due to a lack of a complete health history (30.0%). Willingness to utilize donor gametes if unable to conceive spontaneously was low (31.9%) and few had considered or used donor gametes in the past (12.1%). However, DCP who rated their overall experience as neutral/positive were significantly more likely to be willing to consider using donors themselves if needed (39.8%). Only 1.9% (10) DCP had donated sperm, oocytes, or embryos. DCPs who were donors tended to be less likely to have an ongoing relationship with their own donor (50%) but were no more likely to have an ongoing relationship with a half-sibling(s) from the same donor (85.7%) Limitations, reasons for caution: Because it is not known how many donor-conceived people exist, we don't know what percentage of them have responded to this survey. Wider implications of the findings: People conceived by donor-assisted reproduction are more likely to have neutral to positive overall feelings surrounding their conception if they are told at a very young age about their donor-conceived origins by a family member. Early disclosure should therefore be an integral part of any prospective parent counseling. Trial registration number: Not applicable